Pectins The New-Old Polysaccharides - Alberto Masuelli, Martin (IntechOpen, 2022)
Pectin is an industrial product of certain fruit peels that contain it, such as citrus fruits, apples, pears, grapes, plums, beets, sunflowers, and so on. It is the traditional gelling agent for jams and jellies, but its applications extend to fruit products for food, dairy, dessert, soft drink, pharmaceutical, and other industries. This book discusses pectin production, pectin biotechnology, and pectin applications. Chapters cover such topics as the production of pectin from citrus, fungal pectinases in food technology, pharmaceutical applications of pectin, and more.